Profil Sindrom Aspirasi Mekonium pada Bayi Baru Lahir di RSUD Dr. Soetrasno Rembang - Ahimsa Yoga Anindita; Dwi Hidayah; Yulidar Hafidh; Annang Giri Moelyo; Mayasari Dewi (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: The presence of meconium in amniotic fluid occurs in 13% of live births in developing countries. This condition develops when the gestational age increases at delivery. Meconium aspiration syndrome occurs in 5% of newborns in meconium stained amniotic fluid. The aim of this study is to determine the profile of newborns who experience meconium aspiration syndrome (MAS) who are treated at Dr. Soetrasno Hospital, Rembang and its outcome.Methods: Prospective study, data were obtained from medical records of Dr. Soetrasno Hospital, Rembang during September to October 2018, on newborns with MAS.Results: Of 12 newborns with MAS were obtained, consisting of 7 (58.3%) male and 5 (41.7%) female. All cases were term infants (gestational age above 37 weeks) and normal birth weight (above 2500 grams). Based on the first minute APGAR score, there were 4 newborns had score 1 and 2, respectively (33.3%). Based on the fifth minute APGAR score, there were 7 newborns had score 3 (58.3%). The outcome of newborns with MAS were 7 alive (58.3%) and 5 died (41.7%).Conclusion: There were 12 newborns suffering from MAS (54.5%) of 22 babies hospitalized at the NICU dr. Soetrasno Hospital Rembang. All newborns with MAS were term infants and normal birth weight. There were 5 newborns with MAS which required invasive mechanical ventilation (intubation) and all died (41.7%).